The Effects of Communication on Technological Innovation - Ebadi, Yar M.; Utterback, James M. (Management Science, 1984)
This study examined the relationship between communication and technological innovation. It focused on the patterns of technical communication among researchers and organizations to find out if these patterns had any effect on the success of technological innovation. The objectives were to: (1) investigate the effects of communication on technological innovation at an individual level, and (2) study the effects of interorganizational communication on technological innovation. Data were gathered from the principal investigators of 117 Sea Grant research projects, which were randomly selected from a sampling frame of 495 projects. Bivariate correlation, and partial correlation, were employed in analyzing the data. The findings indicate that at the individual level, the frequency, centrality, and diversity of communication all have positive effects on the success of technological innovation. However, the frequency of communication was found to have a greater effect than either centrality or diversity of communication on technological innovation. It was also found that high formality of communication had a negative effect on technological innovation. On the aggregate level, network cohesiveness, centrality, and diversity of communications all were positively related to technological innovation. Several managerial implications may be suggested. These implications include management attempts to facilitate and promote exchange of information among researchers and among organizations, joint research projects and other interactive activities.